Asian women’s participation in the synodal process - Brazal, Agnes M. (Theology, 2024)
This article aims to explore to what extent Asian women’s participation in the current synodal process has opened up space towards the recognition of their concerns in the Catholic Church. While encouraging broad participation, discussion on taboo issues and local synodal initiatives, it remains to be seen whether this synodal process will usher in the radical reform or transformational level of participation women want to see in the church.